Assessing the Individual Interviewer Rapport-Building and Supportive Techniques of the R-NICHD Protocol - Tamm, Anett; Otzipka, Jana; Volbert, Renate (Frontiers in Psychology, 2021)
The use of the rapport-building and supportive techniques formulated by the R-NICHD protocol is intended to support children and increase the quality of their statements as well as disclosures without possessing suggestive potential. While the effectiveness of the entire R-NICHD protocol for children who have actually experienced child sexual abuse (CSA) has been supported by research, to date no study assessed the effect of each individual socio-emotional interview technique in both interviewees with and without CSA experiences. The current study aimed to address this gap in research by means of an online vignette-study, asking participants to rate the identified rapport-building and supportive techniques on the scales well-being, willingness to talk, and perceived pressure. A total of 187 participants were randomly assigned to either a hypothetical “abused” or a hypothetical “not abused” group by means of a vignette-manipulation. The results suggest that many socio-emotional interview techniques were perceived as supportive and non-suggestive, while a number of techniques were perceived as not supportive but suggestive. Few differences emerged between the hypothetical “abused” group and the hypothetical “not abused” control group. To conclude, most but not all rapport-building and supportive techniques proposed by the R-NICHD protocol had a positive effect on interviewees.